Numerical Simulation of Nozzle Flow Field with Secondary Injection Thrust Vector Control - Noaman H.R.; Bin Tang Hai; Khalil Elsayed (MATEC Web of Conferences, 2018)
Numerical simulations are performed to characterize the secondary injection thrust vector control. For this objective the following measurements were taken: considering the flow to be compressible and turbulent using Realizable k-ε turbulence model accompanied by enhanced wall treatment, the comparison between the CFD results and the experimental results shows a very good agreement. Then a parametric study on injection mass flow rate (changing secondary stagnation pressure) with the same injection location and injection angle is done. The results stated that increasing the injectant mass flow rate lead to shock impingement from opposite wall at secondary stagnation pressure 1.4 of the primary stagnation pressure.